2015
DOI: 10.1016/j.jhealeco.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Unintended effects of reimbursement schedules in mental health care

Abstract: We evaluate the introduction of a reimbursement schedule for self-employed mental health care providers in the Netherlands in 2008. The reimbursement schedule follows a discontinuous discrete step function-once the provider has passed a treatment duration threshold the fee is flat until a next threshold is reached. We use administrative mental health care data of the total Dutch population from 2008 to 2010. We find an "efficiency" effect: on the flat part of the fee schedule providers reduce treatment duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Several studies address marginal reimbursement incentives induced by discontinuously increasing prospective payment. Douven et al [18] found that mental health-care providers respond to discontinuously increasing reimbursement schedules by expanding the treatment duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies address marginal reimbursement incentives induced by discontinuously increasing prospective payment. Douven et al [18] found that mental health-care providers respond to discontinuously increasing reimbursement schedules by expanding the treatment duration.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing discontinuous reimbursement schedules and their impact on treatment duration and LOS have also been subject to analysis. Douven et al [18] evaluate the introduction of a discontinuous reimbursement schedule for self-employed mental health-care providers in the Netherlands. They find that providers respond to price incentives by treating patients longer to surpass a treatment duration threshold.…”
Section: Introductionmentioning
confidence: 99%
“…The main idea of policy research by Douven et al (2015) is to evaluate the performance-based payment schemes for self-employed mental health-care providers using the large mental health institutions as a control group. Douven et al use administrative data from the Dutch health-care authority covering the years 2008 to 2010.…”
Section: Evaluation Of Performance-based Payment Schemes In Mental Hementioning
confidence: 99%
“…These large mental health institutions receive an annual budget, and their employees, including psychiatrists, psychologists and mental health-care nurses, receive a fixed salary. The main idea of policy research by Douven et al (2015) is to evaluate the performance-based payment schemes for self-employed mental health-care providers using the large mental health institutions as a control group. Douven et al use administrative data from the Dutch health-care authority covering the years 2008 to 2010.…”
Section: Evaluation Of Performance-based Payment Schemes In Mental Hementioning
confidence: 99%